Obesity among health care workers in Pahang and its association with job categories - Kunyahamu, Muhammad Syafiq (2020)
Background: Burden of obesity among health care workers will affect the health service given either directly or indirectly as well as the HCWs health. Furthermore, different types of job categories are believed to have different risks to develop obesity. There have been multiple methods and strategies implemented by the Ministry of Health (MOH) as a result of the increased rate of obesity among workers in Malaysia, including the KOSPEN Plus program, which aims to promote a healthy lifestyle among staff. Objective: To determine the prevalence and characteristics of obese HCWs in Pahang and its association with the job category. Methodology: This study was conducted using a cross-sectional method that was derived from the secondary data of the KOSPEN PLUS health screening program involving all job categories government HCWs in Pahang. BMI was calculated for each individual subject. The association of obesity among HCWs with different job categories were then identified using multiple logistic regression. Results: The samples extracted from the data were 4241(94.47%) after considering inclusion and exclusion criteria. Two hundred and forty-eight samples were incomplete with missing of weight or height or BMI data. Descriptive and multiple logistic regression analysis were performed. From all of the subjects collected, 1405 (33.1%) of the HCWs were overweight, and 892 (22.1%) were obese. Compared to the three job categories, nurses contribute half of the subject in obese groups (50%) while doctors 7.6% and other job categories 42.4%. From multiple logistic regression, only the variable job categories and co-morbid were significantly associated with obesity among HCWs. In terms of association with the job category, the result has shown that being a nurse has 1.91 times the odd (95%CI 1.45,2.53) to become obese compared to a doctor when adjusted for co-morbid. Being other job categories has 1.63 times odd (95%CI 1.23,21.6) to become obese compared to the doctor when adjusted for co-morbid. Conclusions: The burden of obesity among HCWs in Pahang was higher than the general adult population in Pahang. The job category was significantly associated with obesity, and nurses were found to have a higher risk of developing obesity than doctors and other job categories. There is a need to improve the obesity status of these HCWs in view of their roles as health advocators within the community. More efficient intervention and policy implementation programs need to be done to tackle this issue.